Johann Christian of Swéerts-Sporck and Franz Girtler − Together on a Journey between Piety and Economic Interest - Čapská, Veronika (Theatrum historiae, 2012)
The article explores the interconnectedness of a noble family with one lineage of their patrimonial officials. The author argues that the grand tour undertaken in 1750−1752 by Johann Christian of Swéerts-Sporck (1729−1802) in company of his economic assistant Franz Girtler was essential for establishing a close tie between the young nobleman and his future prominent official. The journey itself was quite atypical as it had surprisingly strong features of a pious pilgrimage. An extensive group of preserved sources consisting e.g. of a hand-written travel diary, notebooks and printed spiritual biographies enables an in-depth analysis of both devotional and economic context of the rise of the Girtler officials in the service of the Swéerts-Sporck family.